The Protective Effect of Kentut Leaf Extract (Paederia foetida L.) on Gastric Histopathology in Escherichia coli-Infected Sepsis Mice Model - Savitri, Lisa; Kasimo, Elfred Rinaldo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Sepsis, a severe medical condition, signifies the systemic immune response to infection, often leading to organ dysfunction and mortality. Escherichia coli is a significant contributor to sepsis cases, particularly in gastrointestinal disorders. This study aimed to investigate the histopathological changes in the gastric tissue of mice induced by Escherichia coli infection and evaluate the protective effects of kentut leaf extract (Paederia foetida L.). Histopathological analysis revealed distinct alterations in the gastric tissue among different treatment groups. While normal mouse treatment showed no significant changes, negative control (K-) and positive control (K+) groups exhibited inflammation and hyperemia of the gastric mucosa, characterized by necrosis, degeneration, and inflammatory cell infiltration. Treatment with kentut leaf extract (P1, P2, and P3) resulted in milder inflammation compared to controls, indicating a protective effect against gastric mucosal damage induced by Escherichia coli infection. This protective mechanism is attributed to the anti-inflammatory properties of saponins, flavonoids, and essential oils present in kentut leaf extract. These findings underscore the potential therapeutic benefits of kentut leaf extract in mitigating gastric mucosal injury associated with bacterial infection.